HYPOKALEMIA AS A NEGLECTED CAUSE OF METABOLIC BONE DISEASE: TWO CASE REPORTS - Hardigaloeh, Amanda; Yunir, Em; Tarigan, Tri Juli Edi; Lydia, Aida; Anggoro, Suryo; Agung, Ibrahim (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Hypokalemia occurs secondary to several possible causes that ultimately lead to excessive potassium loss in the body. Long-standing hypokalemia via renal losses could lead to metabolic bone disease (MBD). CASES We report two cases of young patients who came in due to fractures. Both patients had a history of lower extremity paralysis. Biochemical analysis showed chronic hypokalemia and metabolic acidosis with normal anion gap, suggestive of renal tubular acidosis (RTA). Patient 1 had impaired renal function with a normal vitamin D level, while patient 2 had normal renal function but had low vitamin D. Genetic testing for RTA could not be performed due to resource constraints. Their MBD was confirmed by radiological assessment. Treatment of both patients involved correction of the acidosis and physical rehabilitation without the need for orthopedic intervention. RTA is the most common cause of hypokalemia. It is characterized by a normal anion gap metabolic acidosis and renal potassium wasting. Chronic uncorrected acidosis could increase RANKL expression that will promote the differentiation of osteoclasts, leading to increased bone resorption. The most common skeletal manifestations of uncorrected RTA are rickets or osteomalacia, fracture, pseudofracture, secondary osteoporosis and sclerotic bone disease. Since our two patients came in with severe MBD, it would be difficult to reverse these changes and revert to optimal skeletal function. CONCLUSION In a patient with chronic hypokalemia and metabolic bone disease, RTA must always be considered as a cause. Increasing awareness regarding the causes of hypokalemia and its long-term impact on the body may facilitate early diagnosis and treatment, thereby preventing permanent sequelae such as MBD.